2013
DOI: 10.1111/anae.12384
|View full text |Cite
|
Sign up to set email alerts
|

Modelling propofol pharmacodynamics using BIS-guided anaesthesia

Abstract: SummaryUsing Schnider's pharmacokinetic model, propofol pharmacodynamics were modelled during total intravenous anaesthesia. The method involved adjusting a pharmacokinetic/pharmacodynamic model according to data obtained from 42 patients having operative procedures with remifentanil analgesia. Parameters C e50 and c were estimated for induction and maintenance by analysing patients' bispectral index. The pharmacodynamic models were different for induction and maintenance. The mean (95% CI) C e50 for induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…25 In 2013, Martín-Mateos and colleagues showed that BIS values fluctuate around an index of 50 and that this fluctuation varies among patients. 26 In our study, approximately 50% of patients demonstrated low BIS values, and in five of these patients, the EEG showed a burst suppression pattern, which signifies overly deep anaesthesia.…”
Section: Discussionsupporting
confidence: 46%
“…25 In 2013, Martín-Mateos and colleagues showed that BIS values fluctuate around an index of 50 and that this fluctuation varies among patients. 26 In our study, approximately 50% of patients demonstrated low BIS values, and in five of these patients, the EEG showed a burst suppression pattern, which signifies overly deep anaesthesia.…”
Section: Discussionsupporting
confidence: 46%
“…Where, EC 50 represents the value of the brain concentration in ug/ml to achieve loss of consciousness after bolus dose. λ is the steepness of brain concentration versus response curve [23,26]. If these parameters are known, the dose required to achieve the target BIS signal can be calculating.…”
Section: Drug Sensitivity Parameters Estimationmentioning
confidence: 99%
“…For instance, a linear relation is found between age and EC 50 [70]. Cardiac output (CO) [3,108] and administration mode (bolus or infusion) [91] were also found to influence the time and dose required for propofol anaesthesia.…”
Section: Model Uncertaintymentioning
confidence: 99%